Agrochemical Residues in Soil, Water, Chicken’s Blood and Worker’s Urine Samples in Rose Farms, Tak Province, Thailand - Jittima Hirunrussamee (2022)
The agrochemical overuse, especially that of paraquat, cypermethrin and carbendazim, has been observed in Thailand. Residuals do not only contaminate the environment and agricultural products, but also other living organisms related to the farming. With less attention being paid to the agrochemical residues in the environment, this study aimed to quantify agrochemical residues in soil, water, chicken’s blood and worker’s urine samples across different periods of cultivation among nine rose farms in Tak Province, Thailand were selected as study sites. Various agrochemicals were used throughout the year; particular attention was paid to paraquat, cypermethrin and carbendazim. Soil and water samples represented the environment, chicken’s blood represented animal subjects, and urine samples of rose farmers represented human subjects. The study revealed the existence of those three agrochemical residues in both soil and water samples. It was only in soil samples that paraquat and cypermethrin concentrations were higher than the maximum allowable concentration (47.24 mg kg-1 and 0.24 mg kg-1, respectively). Residues of cypermethrin and carbendazim were found only in chicken’s blood (0.0280 µg L-1 and 0.0750-0.1640 µg L-1, respectively). Since rose farmers were well equipped with personal protective equipment when applying the pesticides, paraquat, cypermethrin and carbendazim quantifications in their urine samples were all below the detectable limits of the instruments used. Further studies such as better methods for residue analysis and a larger sample size are needed. More reliable quantifications may possibly result in assessing the relationship between agrochemical residues among environmental and living organisms.